Feasibility of a Semi-computerized Line Bisection Test for Unilateral Visual Neglect Assessment - Jee, H.; Kim, J.; Kim, C.; Kim, T.; Park, J. (Applied Clinical Informatics, 2015)
Background: Commonly used paper-and-pencil based test modalities for assessing the degree of unilateral visual neglect (ULN) in patients with hemispheric cerebral lesions consume human resources with a significant inter and intra-rater variability.Objective: To explore the feasibility of a semi-computerized electronic-pen based ULN assessment system (e-system) to improve assessment quality without altering the conventional user interface.Materials and Methods: Thirty cognitively healthy participants (HG) and 11 participants diagnosed with right-hemispheric lesion and unilateral visual neglect (NG) were recruited to evaluate the e-system. Line bisection tests (LBT) were repeatedly conducted twice for the inter-rater and intra-rater (reliability) comparisons. The LBT results were assessed by the e-system and the golden standard methods (manual rater assessment). The percent deviation (%), assessment duration (sec), and number of neglected line (each) were evaluated.Results: The inter-rater comparisons of the assessed deviation (%) variable showed excellent inter-rater reliabilities (CCCs) ranging from .84 (.59 to .95 (p < .001)) to .99 (.90 to .99 (p < .001)) for HG and NG. The Bland Altman mean difference (B-A) plots with bias (95% LOA (limits of agreement)) showed similar agreements between the e-system and the raters ranging from -.04 % (-2.10 to 1.97) to 1.30 % (-2.23 to 4.84) for HG and NG. The effect sizes (ES), which show similarities between the assessment methods, yielded smaller ranges from .01 to .30 for HG and NG. The reliability (test-retest) comparisons showed similar assessment results between the e-system, rater 1, and rater 2. The manual rater assessment time ranging from 5.85 to 6.00 minutes and inter- and intra-assessment variations were virtually eliminated with the e-system.Conclusion: The semi-computerized system with the conventional paper-and pencil user-interface showed valid and reliable assessment results. It may be a feasible replacement for the manual rater assessment modality even in a clinical setting.Citation: Park J, Jee H, Kim C, Kim J, Kim T. Feasibility of a Semi-computerized Line Bisection Test for Unilateral Visual Neglect Assessment. Appl Clin Inform 2015; 6: 400–417http://dx.doi.org/10.4338/ACI-2015-01-RA-0002
Keywords: Unilateral visual neglect; line bisection; computer-aided diagnosis